Modeling and stability analysis of dynamic oscillation behaviors in double‐input Buck/Buck‐Boost DC‐DC converters using frequency selective approach. (22nd September 2020) - Zhang, Hao; Liu, Wei; Ding, Honghui; Meng, Yongpeng; Cui, Donggang
Summary: Different from single‐input single‐output converters, stronger nonlinearity and coupling effect become ones of the most salient characteristics in the multiport DC‐DC converters (MPCs). Therefore, the MPCs can exhibit a great variety of more complex oscillation behaviors in different frequency regimes and seriously endanger system stability. In this paper, a frequency‐selective averaging model is proposed to investigate the low‐ and high‐frequency stability problem in the double‐input Buck/Buck‐Boost DC‐DC converter. At first, to characterize both low‐ and high‐frequency regime dynamics in one unified frame, the short‐time Fourier transform will be applied to obtain a frequency‐selective averaging model. Based on the proposed model, theoretical analysis is performed to identify subharmonic oscillation and low‐frequency oscillation by the movement of the eigenvalue loci. In particular, the underlying mechanism of the subharmonic oscillation and low‐frequency oscillation is uncovered deeply by participation analysis. It shows that period‐doubling bifurcation and Hopf bifurcation result in the subharmonic oscillation and low‐frequency oscillation, respectively. Moreover, some stability boundaries show the influence of varying parameters on system stability thoroughly, which is important to guide system stability enhancement. Finally, some circuit experiments are presented to verify the above theoretical and numerical results. Abstract : In this paper, a frequency‐selective averaging model is proposed to describe both high‐ and low‐frequency dynamics of multi‐input converters and significantly is independent of topology sequences. Based on the proposed model, the underlying mechanism of subharmonic and low‐frequency oscillations is analyzed in detail, and particularly, the evolution of these dynamic oscillation behaviors is identified. In addition, some stability boundaries are given for system stability enhancement.